The Systematic Design and Implementation of a Training Program for Teaching Assistants - Saroyan, Alenoush; Amundsen, Cheryl (Canadian Journal of Higher Education, 1995)
An increase has recently occurred in the number of programs which formally prepare teaching assistants (TAs) for their designated teaching responsibilities. These programs may also be seen as an investment in preparing the future professorate for their teaching roles. This paper describes how a program for the training of teaching assistants was conceptualized and implemented at McGill, a large research-oriented Canadian university. A review of the relevant literature is followed by a detailed description of the systematic approach to program development involving needs assessment, planning and implementation, and evaluation. The relationship between various levels of the University and the way in which these relationships have strengthened the TA training program are highlighted.